Expression of Genes Located on the Incompatibility Group FIB Plasmids at Transcription and Protein Levels in Iron-Modified Growth Conditions - Abbott, Carter N.; Felix, Monique; Foley, Steven L.; Khajanchi, Bijay K. (Frontiers in Microbiology, 2021)
Salmonella enterica strains often harbor plasmids representing several incompatibility groups (Inc) including IncFIB, which have been previously associated with carrying antimicrobial resistance and virulence associated genes. To better understand the distribution of virulence factors, we analyzed 37 complete whole genome and plasmid sequences of different S. enterica isolates from multiple serovars that carried IncFIB plasmids. Many of the sequences analyzed carried multiple virulence-associated genes, including those associated with iron acquisition systems; thus we aimed to determine how iron-rich (IR) and various iron-depleted (ID) conditions affected the transcription of iron acquisition and virulence genes including sitA, iutA, iucA, and enolase at different time intervals. Wild type S. enterica strain SE163A and a transconjugant (SE819::IncFIB) were grown in Luria-Bertani (LB) IR and LBID broth for 2, 4, and 18 h. sitA, iutA, and enolase that were grown in LBID conditions were substantially upregulated when compared to LBIR conditions. For both S. enterica strains that were grown at various LBID conditions, 200 µM bipyridyl had the highest transcription for all four genes, followed by the 100 µM concentration. An antibody using a peptide targeting aerobactin receptor gene iutA encoded by IncFIB was generated and used to examine the protein expression in the wild-type, recipient, and transconjugant strain in LB, LBID, and LBIR growth conditions using Western blot analyses. A 70 KDa protein band was detected in the wild-type and transconjugant that carried the IncFIB plasmid, while this band was not detected in the recipient strain that lacked this plasmid. These data provide valuable information to improve our understanding on the iron regulation of virulence associated factors encoded by the IncFIB plasmids.